Small-angle muon and bottom-quark production in pp̄ collisions at √s = 1.8 TeV - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Akimov, V; Alves, G; Amos, N; Anderson, E; et al. (2000)
The inclusive muon cross section, and the cross section for mouns originating from b quark decay, in the forward rapidity region of 2.4 < | ymu | < 3.2 were measured in this study. It was found that next-to-leading order QCD calculations underestimate b quark production by a factor of 4 in this region.